PENGARUH LATIHAN AGILITY LADDER EXERCISE DAN NEBRASKA AGILITY DRILL TERHADAP KELINCAHAN MENGGIRING BOLA PADA PEMAIN CLUB SEPAKBOLA BOLLIVIA KABUPATEN ENREKANG - Nur Awal; Baharuddin Baharuddin; Saharullah Saharullah (Program Studi Ilmu Keolahragaan FIK UNM, 2022)
The purpose of this study is whether the effect of agility ladder excersice exercises and Nebraska agility drills on the ability to dribble in the game of the Bollivian football club in Enrekang Regency. The type of research that will be used in this research is experimental research. In this research design, research subjects were selected by purposive sampling. Data analysis techniques using SPSS using normality and homogeneity tests, and hypothesis testing. Based on the results of data analysis regarding the effect of the agility ladder exercise and Nebraska agility drill on the ability to dribble the Bollivia football club players, Enrekang Regency. Initial data on the ability to dribble n (sample) 10 people were obtained. The results of the ability to dribble a soccer game, Thit = 4.22 > Ttab(0.05) = 2.26. Because the value of Thit is greater than Ttab, then Ho is rejected. Obtained the average score of the ability to dribble the initial soccer test (X A1 = 19.93) and the average value of the ability to dribble the soccer game after being given the agility ladder training treatment, the final test results were obtained (X A2 = 18.79). This shows that the group between the initial test and the post test has a difference or influence on the results of the ability to dribble in soccer games. In the Nebraska agility drill, the test results for the ability to dribble a soccer game, Thit = 2.91 > Ttab(0.05) = 2.26. Because the value of Thit is greater than Ttab, then Ho is rejected. This means that it can be interpreted that there are real differences in the ability to dribble in soccer games. Obtained the average value of the ability to dribble a soccer game initial test (X A1 = 18.51) and the average value of the ability to dribble a soccer game after being given the Nebraska agility training treatment, the results of the final test of the ability to dribble a soccer game were obtained ( X A2 = 17.56).